An improved HILIC HPLC-MS/MS method for the determination of β-ODAP and Its α isomer in lathyrus sativus - Bento-Silva, Andreia (2020)
This research was funded by EUROPEAN UNION'S SEVENTH FRAMEWORK PROGRAMME for research, technological development and demonstration under grant agreement number 613551 and by FUNDACAO PARA A CIENCIA E TECNOLOGIA (IF/01337/2014, PTDC/AGR-TEC/0992/2014) and PORTUGAL 2020 to the Portuguese Mass Spectrometry Network, grant number LISBOA-01-0145-FEDER-402-022125.